Paléolithique moyen en pays de Caux (Haute-Normandie) Le Pucheuil, Étoutteville : deux gisements de plein air en milieu lœssique - Delagnes, Anne; Ropars, Anne (Documents d'archéologie française, 1996)
The excavations carried out on the lines of the A28 an A29 motorways have brought to light two sites from the Middle Palacolithic (-300 000 - -30 000). The desposits at Pucheuil and at Etoutteville (Haute-Normandie) yielded important lithic series with numerous reassemblies of waste flakes. At Pucheuil, two human occupations were observed in the context of a doline. They ear individualized by their particular technological traditions which both stem from the santé chain of production : the Levallois technique. This, in association with a volumetric conception of the nucleus which resembles those of the Upper Palaeolithic, characterises the laminar production of Etoutteville. The spatial analysis of the reassembled groups of material identify the site as a knapping workshop. These results, complemented by a presentation of the geomorphological and stratigraphical frameworks, represent a solid contribution to our knowledge of the Prehistory of north-west Europe.